Nutritive value and utilization of Baobab (Adansonia digitata) seed meal as plant protein source in the diet of juveniles of Clarias gariepinus (Burchell, 1822) (Pisces: Clariidae) - Anene, Afamdi; Afam-Anene, Olivia C.; Onyekachi, Chisom (Journal of Research in Biology, 2012)
This paper aimed at evaluating the potentials of boiled Baobab (Adansonia digitata) seed meal as plant protein source in the diet of juveniles of Clarias gariepinus. A sixty-day feeding trial was conducted in 40L plastic aquaria tanks. Boiled baobab seeds meals were incorporated in diets at 0, 25, 50, 75 and 100% designated as diets D1 (Control), D2, D3, D4 and D5 respectively. All diets were iso-nitrogenous and iso-caloric. Juvenile Clarias gariepinus with initial mean weight 101.24±34g were fed ad lib on allotted diets twice per day for 60 days. Mean body weight gain in fish fed on D1 was highest with a value 901.22g and lowest in Diet 5 with a value of 250.39g. The mean daily weight gain in fish was highest in Diet 1 with a value of 15.4% and lowest in Diet 5 with a value of 4.17%. Specific Growth rate (SGR) of experimental fish was highest with a value of 3.62% in Diet 1 and lowest in Diet 5 with a value of 2.09%. Proximate composition of fish fillets fed on test diets show that the protein level in diet 21.88±0.11% in Diet 3 and 21.00±1.00% in D4 were significantly higher than the other diets while the crude fiber was highest in Diet 4 with a value of 2.90±0.17% and lowest in Diet 3 with a value of 1.93±0.12%. This study shows that up to 25% of boiled baobab seeds can be incorporated into the diets of juvenile C. gariepinus without any negative effects on growth of fish.